2019
DOI: 10.1002/chem.201902981
|View full text |Cite
|
Sign up to set email alerts
|

A Low‐Temperature Approach for the Phase‐Pure Synthesis of MIL‐140 Structured Metal–Organic Frameworks

Abstract: In as ystematic investigation,t he synthesis of metal-organicf rameworks (MOFs) with MIL-140 structure was studied. The precursors of this family of MOFs are the same as for the formation of the well-known UiO-typeM OFs although the synthesis temperature for MIL-140 is significantly higher. This study is focused on the formationo fZ rbased MIL-140M OFs with terephthalic acid (H 2 bdc), biphenyl-4,4'-dicarboxylic acid (H 2 bpdc), and4 ,4'-stilbenedicarboxylic acid (H 2 sdc)a nd the introduction of synthesis fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…Another possibility could be that lowering the pH increases the possibility of linker protonation on the formed MOFs themselves, adding additional reversibility to the process and the thermodynamic F4_MIL-140A(Ce) to be formed, as suggested in a recent paper reporting a systematic investigation of the influence of several parameters on the crystallisation of phase pure MIL-140 type MOFs in DMF solvent. [16] However, the evidence in our hands does not indicate that a more acidic environment promotes such a dissolution-recrystallisation process.…”
Section: Effect Of the Amount Of Hno3contrasting
confidence: 69%
“…Another possibility could be that lowering the pH increases the possibility of linker protonation on the formed MOFs themselves, adding additional reversibility to the process and the thermodynamic F4_MIL-140A(Ce) to be formed, as suggested in a recent paper reporting a systematic investigation of the influence of several parameters on the crystallisation of phase pure MIL-140 type MOFs in DMF solvent. [16] However, the evidence in our hands does not indicate that a more acidic environment promotes such a dissolution-recrystallisation process.…”
Section: Effect Of the Amount Of Hno3contrasting
confidence: 69%
“…This could be due to the role of HNO 3 in inhibiting deprotonation of AcOH and its coordination to Ce IV to form the hexanuclear [Ce 6 O 4 (OH) 4 (‐COO) 12 ] clusters needed for the F4_UiO‐66(Ce) phase. Another possibility could be that lowering the pH value increases the possibility of linker protonation on the formed MOFs themselves, adding additional reversibility to the process and allowing the thermodynamic product F4_MIL‐140A(Ce) to be formed, as suggested in a recent paper reporting a systematic investigation of the influence of several parameters on the crystallisation of phase‐pure MIL‐140 type MOFs in DMF [16] . However, the evidence in our hands does not indicate that a more acidic environment promotes such a dissolution–recrystallisation process.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently shown that addition of 10 equivalents of AcOH to a DMF-based reaction mixture otherwise affording pure MIL-140A(Zr), a mixed MIL-140A/UiO-66 product is formed. [16] Further increasing the amount of acetic acid up to 30 equivalents appears to increase the MIL-140/UiO-66 ratio. These results may suggest that, at least in DMF solvent, the coordination modulator can in fact favour the thermodynamic product also in the MIL-140/UiO-66 system.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…S1 †). 22 This MOF shows a high thermal and chemical stability which can be compared to the former reported MIL-140 MOFs. 18 A synthesis for an azo-based MIL-140D-H with H 2 abdc as linker is also described in literature (see ESI Table S1 †).…”
mentioning
confidence: 74%